Aging of Passive Oxide on SUS304 Stainless Steel in a Sulfuric Acid Solution. Issue 8 (1st January 2016) - Ohtsuka, Toshiaki; Ueda, Mikito; Abe, Masatoshi
Abstract : The passive oxide film on SUS 304 stainless steel (SS) was studied in a 0.1 mol dm −3 sulfuric acid solution as a function of passivation time. The passive oxide films were measured by ellipsometry and X-ray photoelectron spectroscopy (XPS). A Mott-Schottky plot of the film capacitance was employed to determine the donor density in the n-type semiconducting oxide film, and current measurements of the Fe 3+ /Fe 2+ redox couple were employed to investigate the electronic transfer process on the passive oxide film. The passive oxide consists of Cr-Fe-Ni oxides in which enrichment of Cr to 57 mol% occurs as the potential increases. During the aging of the passive oxide at 0.6 V vs. Ag/AgCl/saturated KCl (SSC) for 43 ks, the current decreased from 30 μA cm −2 at 10 s to 0.025 μA cm −2 at 43 ks, and the Cr ratio in the oxide increased from 49 to 57 mol% with an increase in the O 2– ratio. Notably, the film thickness remained nearly constant at 1.3 nm during the aging process. Enrichment of the Cr content resulted in a decrease in the donor density of the n-type semiconducting passive oxide and the inhibition of electronic charge transfer from/to the Fe 3+ /Fe 2+ redox couple in the electrolyte.